THE IMMUNOLOGICAL CHARACTERISTIC OF RA PATIENTS WITH ANAEMIA - A. E. Sizikov; V. V. Senyukov; V. S. Kozhevnikov; L. P. Konenkova; E. V. Zonova; M. A. Korolev; N. V. Pronkina; O. A. Herzog; N. V. Pronkina; E. V. Menyaeva; E. V. Evsyukova; V. A. Kozlov (Медицинская иммунология, 2014)
Abstract. The aim of the investigation was to study the immunological characteristics of RA patients with anaemia. Clinical and laboratory data including the percentage of the main lymphocyte subclasses, phagocyte and DTH-effector activity, serum concentration of immunoglobulins, the percentage of cells producing IFNγ and/or IL-4 and percent of monocytes producing TNF. We revealed some significant clinical, laboratory and immunological differences between RA patients and healthy donors and between patients with and without anaemia. Our data demonstrate RA anemic patients to have more severe disorders than patients without anaemia. We also revealed some significant immunological differences between RA patients and healthy donors and between patients with and without anaemia, including percent of cells producing IFNγ and/or IL-4. Our data permit to conclude that RA patients have many different immunological disturbances, more severe in anaemic patients.